Biological Evolution of Titanium(IV) Complex [{(NNO)2Ti}3O3] Bearing Bidentate Heteroditopic Schiff Base Ligand: Synthesis, Structure and Biological Studies - Kottalanka, Ravi K.; Pagadala, Eswar; Loke, Shiva K.; Jeya Rajkumar, S. Rex; Srinivasadesikan, Venkatesan; Ramchandran, Balajee (Asian Journal of Chemistry, 2019)
Titanium(IV)-complex of chemical composition [{(NNO)2Ti}3O3] (2) bearing bidentate heteroditopic Schiff base [(C5H4OH)-N=CH-C4H3-NH] (L1) ligand in titanium coordination sphere was reported and its biological significance was evaluated. The in vitro cytotoxicity of L1 and 2 were evaluated by using MTT assay on cancer cell lines (MCF-7 & A549) and observed significant cytotoxicity. Further, the LDH and NO assay studies on both L1 and 2 on cancer cell lines revealed that the enhanced cytotoxicity compared to standard anticancer drug i.e. cisplatin. The DNA binding studies of tested compounds with Ct-DNA molecule by using UV-visible and fluorescence spectra and molecular docking studies revealed that moderate to good binding interactions with test molecules. Thus, the present work contributes and implies the biological significance of Ti-complex (2) and the correlation between the structure and the biological activities of such Ti-complexes supported by Schiff base systems opens up opportunities for further exploitation of similar biologically active titanium systems.